Textural layers and polyphonic timbre links in electronic dance music - Marchiano, María (2018)
Polyphonic timbre refers to the overall timbral mixture in a music signal. Some of their most salient acoustic dimensions are the Sub-Band Fluxes. Our hypothesis is that there is a temporal alignment between Sub-Band Flux changes and perceived textural layers’ onsets and offsets in electronic dance music (EDM). (i) We asked to 15 professional musicians to record in Reaper every perceived textural layer’s onset or offset of 11 EDM’s tracks, (ii) and calculated the transitional temporal data between homogeneous and successive states of Sub-Band Flux from signals with MIRToolbox functions. Data (i) and (ii) are being correlated. We expect that acoustical timbral changes will show temporal coincidence with perceived textural layers’ onsets and offsets. Results are still in process, and will be discussed in reference to the EDM’s acoustic environment to mutually afford the perception of textural layers and polyphonic timbres.